MENINGKATKAN PENGETAHUAN TENTANG BUBUR KACANG HIJAU UNTUK BALITA DENGAN STATUS GIZI BGM (BAWAH GARIS MERAH) DI PERKUMPULAN YASINAN KELUARGA USWATUN KHASANAH DI DESA TARUB KECAMATAN TAWANGHARJO KABUPATEN GROBOGAN - Purhadi (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Toddlers with a low birth weight (BGM) are those whose weight falls below the red line on the Child Health Card (KMS). BGM are toddlers with growth disorders and require special attention, including supplementary feeding and counseling. Mung bean porridge is a food made from mung beans, due to its high vegetable protein content. Objective: Participants will improve their knowledge and skills in making mung bean porridge. Method: This program uses a scientific lecture method, as well as practical cooking techniques for making mung bean porridge and pudding. Results: Evaluation was conducted by asking participants questions about the theory of making mung bean porridge. All mothers present were able to answer questions about the theory and practical observations of making mung bean porridge. Conclusion: The knowledge dissemination and demonstration of making mung bean porridge for BGM (below the red line) nutritional status activities were very effective in increasing participants' knowledge because they included demonstrations on how to make mung bean porridge correctly.